Taking the Back off the Watch, A Personal Memoir of Thomas Gold: 381 (Astrophysics and Space Science Library) by Thomas Gold edited by Simon Mitton - Sturrock, Peter (Journal of Scientific Exploration, 2017)
Taking the Back off the Watch, A Personal Memoir of Thomas Gold: 381 (Astrophysics and Space Science Library) by Thomas Gold edited by Simon Mitton. Berlin/Heidelberg: Springer, 2016. 252 pp. $49.69 (rented Kindle). ISBN 3642275877. Early in my career at Stanford, in the course of a conversation with Leonard Schiff (then the Department Chair), I asked him what he considered to be the most important characteristic of a successful scientist. He replied “Strength of character.” Thomas Gold (always known as Tommy) had that characteristic in spades. He was not a physicist, nor a biologist, nor a geologist, nor a space scientist, nor an astrophysicist, nor a cosmologist – he was all of the above. My first encounter with Tommy was in 1953, at a conference on “Gas Dynamics of Cosmic Clouds” in Cambridge. There was discussion about the geomagnetic storms, and their various components – the Sudden Commencement, the Main Phase, etc. No one was offering any convincing theoretical interpretation of these phases, when up spoke someone with a clear and confident voice. He argued that the only way to understand how the “sudden commencement,” with a time scale of minutes, could be initiated by a solar flare that had occurred perhaps a day earlier, was to attribute the sudden commencement to a shock wave that had traveled ahead of the material ejected by the flare (material which would subsequently initiate the main phase). He then went on to point out that it could not be a conventional hydrodynamic shock, because the mean-free path of the atoms, electrons, and ions was far too long to lead to a shock wave duration of just minutes. It had to involve the interaction of the electrically conducting gas with magnetic field. Once stated, the interpretation was obvious! But it took someone with the intelligence, curiosity – and strength of character – of Tommy Gold to see it.